MODERASI NPL TERHADAP PENGARUH EFISIENSI OPERASIONAL, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN EMITEN PERBANKAN BEI - Lumbanraja, Maha Martabar Mangatas; Halim, Edyanus Herman; Nainggolan, Bintang Pratiwi (Jurnal Daya Saing, 2025)
This study is motivated by the decline in National GDP seen in terms of trends, on the other hand the banking sector provides an increasing contribution to National GDP but when viewed in terms of proportion, the contribution of the banking sector to GDP has decreased while the value of banking companies seen from the Composite Index has increased every year. This study aims to analyze the effect of operational efficiency, capital structure, and company size on company value with NPL as a moderation. The population in this study includes 47 banking sub-sector companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used the purposive sampling method with a sample size that met the criteria of 42 companies. The type of data used is quantitative data and the data source uses secondary data. The data analysis technique uses SEM PLS with SmartPLS software. This study shows that company size can affect company value. Where company size is a signal that can influence investors' views on the company so that it has an impact on the value of the company. This study also found that NPL is able to moderate the effect of BOPO on company value. Where the presence of high NPL can increase the costs incurred by the bank which has an impact on increasing the BOPO ratio. This research has implications for companies, investors, and academics because it can help in making investment decisions, evaluating company financial performance, developing theories and research for academics or further researchers.